Hubungan Kondisi Geografis dan Lingkungan Sosial terhadap Kejadian Tuberkulosis di Wilayah Kerja Puskesmas Perawatan Satui Tahun 2022 - Muhammad Rizki Hanafi; Eddy Rahman; Husnul Khatimatun Inayah; Erwin Ernadi (Universitas Baiturrahim, 2023)
Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. Tuberculosis cases in the work area of the Satui Health Center are currently increasing with the cases as many as 13 cases in 2020 and has increased so far. This study aims to determine the relationship between geographical conditions and social environment on the incidence of tuberculosis in the work area of the satui care health center in 2022. Survey research method by distributing questionnaires and interviews with case control approach method. The total of samples used is 46 respondents with a total of 23 case respondents and 23 control respondents. The variables of this research were regional classification, economic occupation, knowledge and habits. Statistical test using Chi-Square test. The results of test show that there is a relationship between the independent variable and the dependent variable. The test results show that there is a relationship between the independent variable and the dependent variable. The result of test show that there is a relationship between regional classification (p-value = 0.025), occupation (p-value = 0.018), and economy (p-value = 0.003) with the incidence of Tuberculosis. Suggestion for the community to be able to get used to doing PHBS such as using masks in public places, using masks when sick with coughing, covering mouth when coughing and others. By getting used to doing good PHBS, individuals are not easily infected and do not transmit the seeds of disease.